2007
DOI: 10.1002/biot.200700087
|View full text |Cite
|
Sign up to set email alerts
|

Function of the SIRT1 protein deacetylase in cancer

Abstract: The NAD(+)-dependent protein deacetylase SIRT1 is linked to cellular survival pathways by virtue of keeping the tumor suppressor gene p53 and members of the forkhead transcription factor family deacetylated. To validate SIRT1 as a therapeutic anti-cancer target, we performed immunohistochemistry experiments to study the in vivo expression of SIRT1 in cancer specimens. We show that human SIRT1 is highly expressed in cancer cell lines as well as in tissue samples from colon carcinoma patients. Interestingly, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
176
2
4

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 210 publications
(189 citation statements)
references
References 40 publications
7
176
2
4
Order By: Relevance
“…To examine whether SIRT1 expression is altered in human cancers, we have tested the expression levels of SIRT1 in breast and ovarian cancers. Consistent with the earlier studies that SIRT1 is overexpressed in cancer cell lines and various cancers (Huffman et al, 2007;Stu¨nkel et al, 2007), we found that the levels of SIRT1 are elevated in both ovarian and breast cancers ( Figure 6 and data not shown). Interestingly, SIRT1 levels inversely correlate with the levels of acetylated cortactin in breast tissue specimens, further suggesting that SIRT1 is one of the deacetylases for cortactin in vivo.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…To examine whether SIRT1 expression is altered in human cancers, we have tested the expression levels of SIRT1 in breast and ovarian cancers. Consistent with the earlier studies that SIRT1 is overexpressed in cancer cell lines and various cancers (Huffman et al, 2007;Stu¨nkel et al, 2007), we found that the levels of SIRT1 are elevated in both ovarian and breast cancers ( Figure 6 and data not shown). Interestingly, SIRT1 levels inversely correlate with the levels of acetylated cortactin in breast tissue specimens, further suggesting that SIRT1 is one of the deacetylases for cortactin in vivo.…”
Section: Discussionsupporting
confidence: 93%
“…SIRT1, although mainly localized in the nucleus, can be shuttled to the cytoplasm (Tanno et al, 2007). A recent study showed that human SIRT1 is highly expressed in the cytoplasm in tissue samples from colon carcinoma patients (Stu¨nkel et al, 2007). SIRT1 was present in the cytoplasm in pancreatic islet a and b cells (Moynihan et al, 2005) and was also found to be cytosolic in C2C12 myoblast cells after differentiation (Tanno et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…malignancies (6,42), and changes in SIRT1-mediated signaling allows mammalian cells to survive under oxidative stress and DNA damage, which are closely associated with tumorigenesis (43,44), cancer progression and poor prognosis in cancer patients (3,4,36). The present study identified an association of SIRT1 overexpression with shorter OS time and poor prognostic indicators in SCC, which was consistent with the results of previous studies (4,36,45).…”
Section: A B C Dsupporting
confidence: 92%
“…SIRT1 expression is significantly elevated in prostate and colon cancers (Huffman et al, 2007;Stunkel et al, 2007), and HIC1 (hypermethylated in cancer 1), an inhibitor of SIRT1 transcription, is epigenetically silenced in many tumors (Chen et al, 2005). SIRT1 has however in addition to H4K16 been shown to be a protein deacetylase, and plural effects of SIRT1 on cell survival have been reported.…”
Section: Discussionmentioning
confidence: 99%